Academics’ motivation to research: a study on public universities in Panama - Barsallo, Gabisel; Mendoza, Elisa; Arboleda, Maritzabel; Torreiro-Casal, Monica; Ordoñez, Ciara (Frontiers in Education, 2025)
This article shows an analysis of the factors that motivate and demotivate Panamanian academics (professors and researchers) to carry out scientific research. A descriptive quantitative analysis based on data collected through the ENACT survey is presented. The study gathered data using an online self-administered questionnaire, employing a non-probabilistic and voluntary sampling design. A total of 921 academics from four public universities in Panama provided their consent to participate in the study. Multivariate interdependence methods such as the chi-square test and exploratory factor analysis (EFA) were used to determine relationships between variables. The results showed that within the academics’ occupational landscape, the utilization of new technology, intellectual stimulation, academics’ contributions to society, science through problem-solving, and helping humanity are the key drivers of research motivation. Labor-related aspects, including class schedules and timetables, institutional bureaucracy, wages, lack of opportunities, and job stability, were identified as major demotivating influences. It is recommended that more specific policies need to be developed with an emphasis on the value of research sustainability as an educational model and tool that benefits both the nation’s current and future generations.